Conservation biology for all - Sodhi, Navjot S.; Ehrlich, Paul R. (Oxford : Oxford University Press, 2010)
'Conservation Biology for All' provides cutting-edge but basic conservation science to a global readership. A series of authoritative chapters have been written by the top names in conservation biology with the principal aim of disseminating cutting-edge conservation knowledge as widely as possible.
Description based on print version record.
Includes bibliographical references and index.
Keywords: Conservation biology; Biodiversity